2019
DOI: 10.3390/ma12101717
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Start Block and Corresponding Influence for Grain Selection during Casting of Single-Crystal Superalloys

Abstract: To figure out the impact of the parameters of a starter block (the diameter D and height H) on grain selection and the selecting mechanism, a spiral selector was measured with optical microscopy (OM) and electron backscatter diffraction (EBSD) during the solidification of Ni-based single crystal (SX) superalloys. In this experiment, starter blocks with diameters of 8 mm, 10 mm, 15 mm, and 30 mm and a height of 30 mm were designed to find the best parameters. Recommendations for optimizing starter block geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Further investigations showed that this caused the slow diffusion of solute and their accumulation at these turns, which decreased cooling and solidification rates and ultimately dendrite coarsening. While many studies regarding grain selectors concentrated on the spiral selector part, one particular study [95] focused on the starter block's impact on DS of single-crystal Ni-based superalloys. e effect the starter block parameters can have on grain selection and the selection mechanism was examined in this study.…”
Section: Research Areamentioning
confidence: 99%
“…Further investigations showed that this caused the slow diffusion of solute and their accumulation at these turns, which decreased cooling and solidification rates and ultimately dendrite coarsening. While many studies regarding grain selectors concentrated on the spiral selector part, one particular study [95] focused on the starter block's impact on DS of single-crystal Ni-based superalloys. e effect the starter block parameters can have on grain selection and the selection mechanism was examined in this study.…”
Section: Research Areamentioning
confidence: 99%